Biomimetic tissue models reveal the role of hyaluronan in melanoma proliferation and invasion. (15th January 2020) - Sapudom, Jiranuwat; Nguyen, Khiet-Tam; Martin, Steve; Wippold, Tom; Möller, Stephanie; Schnabelrauch, Mathias; Anderegg, Ulf; Pompe, Tilo
Abstract : Biomimetic matrix models demonstrate the role of the size-dependent effect of hyaluronan in melanoma progression and reveal an alternative explanation for in vivo findings of hyaluronan dependent melanoma growth. Abstract : Interactions of hyaluronan (HA) and tumor and stromal cells are highly discussed as one of the major contributors in tumor progression and metastasis. The balance of HA in the tissue is highly regulated by two key enzyme classes; hyaluronan synthases (HAS) and hyaluronidases (HYAL). Current reports hint that the HA amount in the tissue is correlated with poor prognosis in melanoma, the most life-threatening skin tumor. In this work, we generated in vivo mouse models with low and high expression of Has2 and used the models for studying melanoma proliferation of the B78D14 melanoma cell line. We found that a strong reduction of HA amount in the skin was correlated to decreased tissue stiffness and a reduction in tumor weight. Since tumor cells have a direct contact to the HA in the tumor and at the stroma interface, we reconstituted different biomimetic in vitro models using fibroblasts derived from a mouse model to recapitulate melanoma cell behavior at the tumor boundary, namely, (i) decellularized fibroblast matrix (FbECM), (ii) fibroblast embedded into 3D collagen matrices (FbColl), and (iii) well-defined HA-functionalized 3D collagen matrices (HAColl). We found no considerable effect of high and low amounts of fibroblast-derived HA in the matrices on melanoma proliferation and invasion. However, HYAL1-treated FbECM and FbColl, as well as HAColl functionalized with low molecular weight HA (34 kDa) promoted proliferation and invasion of melanoma cells in a concentration dependent manner. Our results emphasize the molecular weight specific effects of HA in regulation of melanoma behavior and provide an alternative explanation for the in vivo observation of HA dependent tumor growth.